Interpretasi Investor Non-Profesional atas Implementasi International Financial Reporting Standard (IFRS) 8 dan Pernyataan Standar Akuntansi Keuangan (PSAK) 5 dalam Perspektif Framing Information - Erni Suryandari; Imelda Puspita Arisanti (Universitas Muhammadiyah Yogyakarta, Indonesia, 2017)
This study attemps to determines the effects of variable implementation of IFRS 8 which differs in IFRS 8 positive frame, IFRS 8 negative frame, PSAK 5 positive frame, and PSAK 5 negative frame toward non profesional investor’s interpretation. This experiment study is an experiment with factorial design 2x2 between subject. The subject is 120 participants from accounting undergraduate students of Muhammadiyah Yogyakarta University as a subtitute of non professional investors. Data analysis used to test hypotetical result is multiple regression with additional analysis using SPSS ver. 16. The results show that segment information in IFRS 8 with positive frame positive and significantly affect non professional investor’s interpretation than those in PSAK 5 with positive frame. In contrast, segment information in PSAK 5 with negative frame positive and significantly affect non professional investor’s interpretation than those in IFRS 8 with negative frame. This study proves that assessment and individu interpretation can be affected by framing and Prospect Theory plays a role in option choosing and the assessment. There is no difference in interpretation by investor non professional when the information given such as difference format